HGG-15. Generation of a novel mouse model for brain tumors of the DNA methylation class "GBM MYCN". (3rd June 2022) - Schoof, Melanie; Godbole, Shweta; Walter, Carolin; Dottermusch, Matthias; Albert, Thomas; Ballast, Annika; Göbel, Carolin; Neyazi, Sina; Holdhof, Dörthe; Kresbach, Catena; Blattner-Johnson, Mirjam; Modemann, Franziska; et al.
Abstract: Multiple recent publications have described a highly aggressive subgroup of pediatric glioblastoma, which is clearly separable from other pediatric and adult glioblastoma based on its DNA methylation profile (GBM MYCN). These tumors almost exclusively occur in children and have a median overall survival of only 14 months. Many tumors in this group are driven by MYCN amplifications and harbor TP53 mutations. Otherwise, information about these tumors are still sparse and treatment is ineffective and causes severe side effects in many cases. In order to further investigate the biology and treatment options of these tumors, preclinical models are urgently needed. Here, we describe the generation of hGFAP-cre::TP53Fl/Fl::lsl-MYCN mice, which carry a loss of TP53 and show aberrant MYCN expression in neural precursors of the central nervous system. These animals develop large forebrain tumors within the first 80 days of life with 100 % penetrance. These tumors resemble human GBM MYCN tumors by histology, global gene expression, and DNA methylation. In order to understand the developmental biology and intratumoral heterogeneity, we employed single cell RNA sequencing (scRNAseq) to the murine tumors with first results indicating a resemblance of tumor cells to committed oligodendrocyte precursors. We further show that both murine and human tumor cells are sensitive to AURKA inhibition in vitro, suggesting a potential new therapeutic option for improved patient care. We believe that further characterization and utilization of the model will pave the way to improved treatment strategies for patients with these highly aggressive tumors.